Pengembangan UI/UX pada fitur IVT: Loan Calculator dengan metode Lean UX (Studi Kasus: Lancar by Danamas) - Kevin Virginia Sibuea; Yudhi Windarto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
P2P Lending is part of fintech which can bring together borrowers and lenders with Danamas as a liaison. Danamas comes with the Lancar application by provide 'IVT: Loan Calculator' feature which allows prospective borrowers to find out the amount of collateral to be obtained based on the price of the property they own. During the release of the Lancar platform, the drop-out rate for the 'IVT: Loan Calculator' feature are quite high and users did not complete the loan application process on the Lancar platform. Because of this problem, it is necessary to analyze the user experience to present a safe and reliable application by redesigning the user interface. By using the Lean UX method, the end result of this problem is a design solution for user interface on the 'IVT: Loan Calculator' feature in Lancar application with the main focus are current users and new users. Keywords— User Experience, Lean UX, Redesign